This is that the New Testament development of some Old Testament themes - Bruce, Frederick Fyvie, 1910-90; Fuller Theological Seminary, Pasadena, CA. (Exeter, UK Paternoster, 1978)
Includes bibliographical references and indexes.
Annual Payton Lectures, are given in Fuller Theological Seminary, Pasadena, California, February, 1968
Keywords: Bible. N.T. -- criticism, interpretation, etc